2015
DOI: 10.1111/trf.13248
|View full text |Cite
|
Sign up to set email alerts
|

Predicting storage‐dependent damage to red blood cells using nitrite oxidation kinetics, peroxiredoxin‐2 oxidation, and hemoglobin and free heme measurements

Abstract: Background Storage-dependent damage to RBCs varies significantly. Identifying RBC units that will undergo higher levels of hemolysis during storage may allow for more efficient inventory management decision-making. Oxidative-stress mediates storage-dependent damage to RBCs and will depend on the oxidant : antioxidant balance. We reasoned that this balance or redox tone will serve as a determinant of how a given RBC unit stores and that its assessment in “young” RBC will predict storage-dependent hemolysis. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…We used a spectral deconvolution approach to measure heme-containing species, which we recently showed avoids artifacts associated with widely used and commercially available assays that do not distinguish between free heme and hemoglobin [ 52 ]. Consistent with our previous reports, levels of hemoglobin and free heme were in the hundreds of micromolar range in stored RBC supernatants [ 25 , 52 ]. These levels led to an increase in circulating free hemoglobin, free heme, and NTBI after resuscitation, indicated by these species being elevated after resuscitating mice with stored RBCs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We used a spectral deconvolution approach to measure heme-containing species, which we recently showed avoids artifacts associated with widely used and commercially available assays that do not distinguish between free heme and hemoglobin [ 52 ]. Consistent with our previous reports, levels of hemoglobin and free heme were in the hundreds of micromolar range in stored RBC supernatants [ 25 , 52 ]. These levels led to an increase in circulating free hemoglobin, free heme, and NTBI after resuscitation, indicated by these species being elevated after resuscitating mice with stored RBCs.…”
Section: Discussionsupporting
confidence: 92%
“…Another limitation of these measures is that we sampled segments attached to the bags transfused due to constraints limiting the ability to sample the bags directly. Previous studies have shown that segment levels of free hemoglobin are higher than those of their paired bags, whereas the opposite relationship has been reported for free heme [ 24 , 25 ], suggesting that the relative amount of free heme administered is in fact be higher than shown.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The strengths of our study include the consecutive and unselected sample of medical ICU patients, plasma sampling before and after transfusion, sampling from the RBC storage bag rather than the bag segment appendage, and a patient sample size adequate for multivariable analysis. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%